Maskulinitas dalam sastra dan agama di Tiongkok - Anas Ahmadi (Masyarakat, Kebudayaan dan Politik, 2017)
This study aims to describe masculinity in literature and religion of China. The focus of this study are (1) how is the representation of masculinity in literature and religion in China, (2) how is the representation of the other side of masculinity literature and religion in China, and (3) how is masculinity literature and religion in relation to the relevance of social life in China nowaday. The theory used in this study is masculinity. This study used a qualitative descriptive method-style narrative and autoethnography exposure. Source of data used in the form of (1) literature study classical Chinese literature (Journey to the West, Story Classical Ming Dynasty, and The Plum in the Golden Vase or, CHIN P ‘ING MEI Volume 1: The Gathering) and (2) autoethnography. The results show that masculinity in literature and religion in China is very strong. Masculinity in literature and religion in China comes in the form of leadership, courage, and responsibility; (2) the other side of masculinity literature and religion in China, namely concubinage and dominance in leadership; and (3) the masculinity literature and religion in relation to the relevance of public life represented that China upholds masculinity that looked at the country’s leadership, the leadership of the household, and religious leadership.